STRATEGI DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN IPS DI SEKOLAH MENENGAH PERTAMA PADA MASA PANDEMI COVID-19 - Yuliani, Sri; Hartanto, Dicki; Tohirin, Tohirin (TSAQIFA NUSANTARA: Jurnal Pembelajaran dan Isu-Isu Sosial, 2023)
This study examined strategies in an effort to increase students' interest in learning social studies in junior high schools during the Covid 19 period. The method used in this study is a qualitative method based on relevant references related to strategies to increase students' interest in learning. The results of this study concluded that the teaching strategies used in online learning was only chat only (google form, video, and quiz) and combining online chat and video conferencing (google form, google meet, video, and quiz). The first strategy is by applying Google Form. Google Forms is a Google product that can be used to create tests or online learning assessments. It was found that Google forms were used by all schools to find out student attendance, some shared them in WhatsApp groups whose members were teachers and students and others shared them in Google Classroom. Teachers are advised to learn more online teaching strategies. Teachers are also advised to explore and develop online teaching strategies that were suitable for students. It was also recommended to investigate how online teaching strategies influence learning success, beside it was recommended to explore other problems teachers encounter during the online teaching process.